Síndrome de médula espinal anclada en un cachorro bulldog inglés. Reporte de un caso - Acevedo, Carlos M.; Martínez Z., María Del P.; Ruíz S., Isabel; Ramírez, Víctor L.; Balvin, Dubel; González D., María S. (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary Tethered spinal cord syndrome is a developmental disease diagnosed in human but of rare report in small animal practice. In this report a case of spinal disrafism, spina bifida with menyngocele, tethered cord syndrome and dermoid sinus is described in a four months old English bulldog male, that presented a clinical condition of faecal incontinence, muscular atrophy in pelvic limbs and ataxia. The diagnostic procedure, treatment and evolution of the patient are described. The purpose of this report is to provide the practitioner with diagnostic tools to include a neurological entity as a differential diagnosis when attending a patient presenting clinical signs such as fecal and urinary incontinency, ataxia and pelvic limbs debility, in dogs of breeds predisposed to suffering this syndrome; in addition, to highlight this neurological pathologies that could be under diagnosed in most of the cases. Key words: canine dermoid sinus, canine menyngocele, spina bifida, spinal disraphism, tethered spinal cord.